Epidemiological Study of Oral Cancer Cases Over a 10-Year Period - Trayeemay Acharya; Meenal Jethlia; Mudita Chaturvedi; Sanjeev Sharma; Anuj Paul Maini; Madhavi D. Galale; Jayantika Gupta (Wolters Kluwer Medknow Publications, 2024)
Background: Because it causes high rates of morbidity and death, oral cancer represents a major global public health concern. It is vital to comprehend the epidemiological trends of oral cancer instances to execute efficacious preventive and therapy tactics. Objectives: The objective of this retrospective study was to examine the epidemiological patterns of cases of oral cancer in a tertiary care environment over a period of 10 years. Methods: Retrospective analysis was done on patient records of those who received an oral cancer diagnosis at a tertiary care facility. We collected and evaluated data on treatment methods, clinical factors, and demographics. Results: The study included 300 instances of oral cancer in total. The patients' average age was 58.4 years, and 66.7% of them were men. The majority of patients (66.6%) had advanced-stage cancer when they first appeared, with the tongue being the most common original tumor location (40.0%). Conclusion: In summary, this study sheds important light on the epidemiology of oral cancer patients during a 10-year period in a tertiary care context. The results highlight the significance of focused interventions for oral cancer early detection and prevention as well as the requirement for better access to healthcare services for prompt diagnosis and treatment.